2022
DOI: 10.3389/fcvm.2022.1071701
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcium score on standard of care oncologic CT scans for the prediction of adverse cardiovascular events in patients with non-small cell lung cancer treated with concurrent chemoradiotherapy

Abstract: IntroductionChemoradiotherapy (CRT) has been associated with increased incidence of cardiovascular (CV) adverse events (CVAE). Coronary artery calcium scoring (CAC) has shown to predict coronary events beyond the traditional CV risk factors. This study examines whether CAC, measured on standard of care, non-contrast chest CT (NCCT) imaging, predicts the development of CVAE in patients with non-small cell lung cancer (NSCLC) treated with CRT.MethodsPatients with NSCLC treated with CRT at MD Anderson Cancer Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…5-year overall survival was 25% (95% CI 22-29) (Figure 2). Median survival differed between the CACs groups (univariable pvalue 0.49); in CACs 0, median survival was 28 months (95% CI [23][24][25][26][27][28][29][30][31][32][33][34][35][36], while in CACs 1-99, 32 months (26-40), and decreasing median survival in CACs 100-399 and CACs ≥400, with a median survival of respectively 24 months (95% CI 17-29) and 20 months (95% CI [16][17][18][19][20][21][22][23][24][25][26]. Kaplan-Meier survival estimates for the overall survival grouped by CACs are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5-year overall survival was 25% (95% CI 22-29) (Figure 2). Median survival differed between the CACs groups (univariable pvalue 0.49); in CACs 0, median survival was 28 months (95% CI [23][24][25][26][27][28][29][30][31][32][33][34][35][36], while in CACs 1-99, 32 months (26-40), and decreasing median survival in CACs 100-399 and CACs ≥400, with a median survival of respectively 24 months (95% CI 17-29) and 20 months (95% CI [16][17][18][19][20][21][22][23][24][25][26]. Kaplan-Meier survival estimates for the overall survival grouped by CACs are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…To match a recent study [18], the analysis was repeated with CACs divided into two groups: CACs < 100 and ≥100. The entire analysis was also performed in two additional unplanned analyses: 1) without forcing the CAC into the model and 2) excluding patients with mean tumor dose below 60 Gy.…”
Section: Data Management and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our study demonstrated how readily available CV risk markers, such as the presence of CAC on RT planning CTs and/or LAD radiation dose exposure, can capture additional at-risk patients for CV events. Baseline CAC on RT planning CT scans has been associated with increased risk of major cardiac events in patients with breast 27,28 and lung cancer 9,[29][30][31] , yet CAC assessment prior to initiation of cancer treatment is not routinely performed. Similarly, evidence suggests that cardiac substructure radiation dose exposure, particularly to the left coronary arteries, is a better predictor of MACE compared to whole heart dose (i.e., mean heart dose) and warrants inclusion into the global CV risk assessment of patients receiving cardiotoxic cancer therapies 6, [10][11][12][13] We further characterized the prevalence of CHIP at baseline and after completion of RT.…”
Section: Discussionmentioning
confidence: 99%
“…A baseline Calcium Score quantification on a non-contrast ECG-gated chest CT performed during the cancer staging phase is strongly suggested according to the strong evidence correlation between coronary calcification and increased risk for a major adverse cardiac event. 94 …”
Section: Suggested Workflow For Ctr-cvtmentioning
confidence: 99%